Thinking and reasoning / by Alan Garnham and Jane Oakhill - "Garnham, Alan" (Oxford, 1994)
An introduction to thinking and reasoning that draws on a variety of approaches where relevant, but locates its subject matter squarely within the theoretical framework of modern cognitive psychology and cognitive science. After a brief historical introduction, the volume covers all core areas of thinking and reasoning, including concepts and images, the relation between language and thought, logic and deductive reasoning, induction, hypothesis testing, statistical reasoning, decision making, problem solving, expertise, creativity, everyday thinking, the teaching of thinking skills, and the development of thinking.
Keywords: Thought and thinking